ENVIRONMENTAL AND PEDAGOGICAL INNOVATIONS: DEVELOPMENT OF ECOLOGICAL COMPETENCE IN FUTURE ARCHITECTS IN ORDER TO PRESERVE THE LANDSCAPE AND BIODIVERSITY - A. V. Kozachek; G. L. Ledeneva; N. P. Belyaeva; A. V. Krasnova; D. L. Popova (Юг России: экология, развитие)
Abstract. Aim. The aim is to consider the features of the development of ecological competence of future architects for the conservation of landscapes and biodiversity. Methods. In research, we used narrative, descriptive and experimental methods of investigation. Results. We propose and justify the authorial approach to the methodology of structuring the process of formation of future architects’ look at the problems of conservation of landscapes and biodiversity, the implementation of which is expected to be carried out in three stages: the first stage, as objects for the architectural work in preparing the degree projects we selected disturbed landscapes in the populated areas of the region; the second stage, a student has to offer the architectural methods of solving the problem of restoring the disturbed landscape and biodiversity designated in the first stage; the third stage includes the promotion of environmental architectural ideas in the framework of various scientific, technical and socio-oriented activities. We considered 13 years of experience in testing the proposed approach, which showed its effectiveness both in terms of improving the quality of professional training of environmental architecture students and from the point of view of the need to restore damaged landscapes and biodiversity. Conclusions. The proposed approach makes it possible to solve the problem of development of ecological consciousness in architecture students at the same time and solving specific practical problems on restoration of landscapes and the required level of biodiversity in urban areas, overall resulting in a reduction of environmental and economic damage to urban areas, and lower costs for the implementation of environmental protection measures at restoration of disturbed landscapes.